2012
DOI: 10.1177/0961203312470729
|View full text |Cite|
|
Sign up to set email alerts
|

Autologous haematopoietic stem cell transplantation for systemic lupus erythematosus: data from the European Group for Blood and Marrow Transplantation registry

Abstract: Our data further support the concept of immunoablation and ASCT to re-induce long-term clinical and serologic remissions in refractory SLE patients even in the absence of maintenance therapy. This study also suggests a beneficial effect of ex vivo graft manipulation on prevention of relapses post-transplantation in SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 38 publications
(84 reference statements)
3
47
0
2
Order By: Relevance
“…18,19 However, although only one study 20 specifically addressed the issue, there is a general lack of evidence for CD34+ selection in AD. 11,12,21,22 The exception is a lupus study 19 which provides weak support, suggesting that effects may be disease specific. In our study, graft selection had no impact on the clinical results, especially on the neutrophil engraftment and infections were reported in 30% (19/63) of the CD34+ selected vs 34% (19/56 ) of the non-selected group (P = 0.66).…”
Section: Resultsmentioning
confidence: 99%
“…18,19 However, although only one study 20 specifically addressed the issue, there is a general lack of evidence for CD34+ selection in AD. 11,12,21,22 The exception is a lupus study 19 which provides weak support, suggesting that effects may be disease specific. In our study, graft selection had no impact on the clinical results, especially on the neutrophil engraftment and infections were reported in 30% (19/63) of the CD34+ selected vs 34% (19/56 ) of the non-selected group (P = 0.66).…”
Section: Resultsmentioning
confidence: 99%
“…26,29,32 Contrastingly, in other diseases, particularly IA and SLE, in which biological and other modern therapy has proven highly effective and well tolerated, activity of autologous HSCT has fallen dramatically despite evidence of benefit. 8,10,13 Activity has varied considerably between countries, both overall and per head of population, and in relation to specific ADs. The reasons for this are not clear but potentially explained by the number of at-risk patients Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Similar developments happened worldwide and there have been a large number of retrospective and prospective studies in a wide range of ADs. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] More recently, randomized controlled trials have reported confirming proof of principle in several ADs. [28][29][30][31][32] Despite international guidelines and recommendations, the uptake of HSCT in AD has been highly variable, both geographically and in respect to type of AD.…”
Section: Introductionmentioning
confidence: 99%
“…In EBMT too, positive trends in progression-free and overall survival were noted but the numbers are less encouraging [44,90,100]. The last analysis of 28 patients, transplanted between 2001 and 2008 in eight centers of six countries, using a spectrum of conditioning protocols and with median follow-up of 38 months after transplantation, demonstrated that the 5 year overall survival was 81 ± 8%, disease-free survival was 29 ± 9%, and non-relapse mortality (NRM) was 15 ± 7%.…”
Section: Hct In Systemic Lupus Erythematosusmentioning
confidence: 99%
“…Other procedures of different reduced toxicity of immunoablative but not always myeloablative conditioning were published as well: mini BEAM-like, BCNU/CCNU with intermediate dose of melphalan, ±ATG or alemtuzumab, rituximab, or Cy ± thiotepa or fludarabine, etc. Some could lead to the possibility of performing this procedure in outpatient manner [43][44][45].…”
Section: So What Was Changed?mentioning
confidence: 99%